'Atlantic' and 'Dakota Pearl' chipping potato responses to glyphosate and dicamba simulated drift. (4th February 2022) - Brooke, Matthew J.; Stenger, John; Svyantek, Andrej W.; Auwarter, Collin; Hatterman-Valenti, Harlene
Abstract: Field trials were conducted to determine the effects of glyphosate and/or dicamba simulated drift rates on chipping potatoes ( Solanum tuberosum L.) 'Atlantic' and 'Dakota Pearl.' Sublethal herbicide rates were applied at the tuber initiation stage and consisted of dicamba at 99 g ae ha −1 or glyphosate at 197 g ae ha −1 applied alone or the combinations of dicamba at 20 or 99 g ae ha −1 and glyphosate at 40 or 197 g ae ha −1, respectively. At 7 days after treatment (DAT), the high spray combination of glyphosate plus dicamba resulted in the greatest plant damage (28%). Plant injury from plants treated with the low combination of glyphosate plus dicamba did not differ from the nontreated control. At 21 DAT, visible injury increased to 40% for plants treated with the high combination of glyphosate plus dicamba. Total yield suggested that dicamba and glyphosate caused similar yield reductions as plants that received glyphosate at 197 g ha −1 or dicamba at 99 g ha −1 had lower total yields compared to the nontreated and plants that received the combination of glyphosate (197 g ha −1 ) and dicamba (99 g ha −1 ) had lower total yields compared to plants that received either herbicide alone. However, 'Dakota Pearl' plants were more sensitive to glyphosate at 197 g ha −1 than were 'Atlantic' plants, causing the interaction for most tuber grades. Tuber specific gravity was lower for plants that received glyphosate at 197 g ha −1, dicamba at 99 g ha −1, or this combination, but this reduction would not prevent chip processing. Results reinforce the need for diligence when applying these herbicides in proximity to a susceptible crop, such as chipping potatoes, and the need to thoroughly clean sprayers before application to a sensitive crop.